(untitled) (Research, Society and Development, 2021)
Taro (Colocasia esculenta), like any tuber, lacks the proteins that form the gluten network, making it a possible source of carbohydrates in the production of gluten-free products. This study aimed to enable the production of gluten-free pasta elaborated with taro flour. To help with the pasta structure, egg white was used as a protein source, and the transglutaminase enzyme was used as a processing aid. Pasta was produced with varying the contents of egg white powder (5 to 50% replacement in flour) and transglutaminase (0.005 to 0.05% flour base) according to a complete 2² factorial design containing 7 assays. The pasta was evaluated for pH, instrumental color parameters, cooking properties, and texture. The results were analyzed using Response Surface Methodology. Egg white contributed to increasing the chroma and hue angle, while transglutaminase only increased the chroma. Both egg white and transglutaminase showed a positive interaction effect for cooking time and increased weight of cooked pasta, and a negative interaction effect on firmness. However, these raw materials had no significant effect on the volume increase of the cooked pasta and cooking loss. The lowest contents of egg white and transglutaminase enzyme used in this study have already sufficient to structure the gluten-free pasta elaborated with taro flour, which provides adequate technological characteristics to it.